Cranial Nerve VI Palsy After Dural-Arachnoid Puncture. Issue 1 (March 2016) - Hofer, J.E.; Scavone, B.M.
Abstract : ( Anesth Analg . 2015;120: 644–646) The authors summarized the current literature describing cranial nerve (CN) VI injury after dural-arachnoid puncture. PubMed, Ovid, and Google Scholar were searched for relevant literature, which was limited to human subjects and published in the English language. These sources were supplemented by a search of the bibliographies from identified papers.